Nickel-catalyzed direct synthesis of dialkoxymethane ethers - Subaramanian, Murugan; Bera, Abhijit; Prasad, Bhagavatula L. V.; Balaraman, Ekambaram (Journal of Chemical Sciences, 2017)
A simple and efficient method for the preparation of dialkoxymethane ethers (oxymethylene ethers) from alcohols and paraformaldehyde in the presence of commercially available nickel(II) salt is described. The reaction proceeds readily under neutral, solvent-free conditions using paraformaldehyde as a C-1 source. The present strategy has a broad substrate scope including aliphatic (both primary and secondary) and aromatic alcohols and provides a benign method for the preparation of symmetrical dialkoxymethanes in good yields (up to 89%).

Nickel-catalyzed N-vinylation of heteroaromatic amines via C-H bond activation - Landge, Vinod G.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Organic & Biomolecular Chemistry, 2017)
Here, we report a ligand- and reductant-free nickel-catalyzed N-vinylation of heteroaromatic amines using biorenewable p-cymene as a solvent. This unprecedented cross-coupling strategy has high functional group tolerance (halides, alkoxy, cyano, chiral motif, etc.) and proceeded via C-H bond activation.
Keywords: Alkylation; Amination Reactions; Anilines; Aryl Chlorides; halides; Monoarylation; O Bonds; Precatalyst; Pyrimidines; Removeble Directing Group

Room-temperature direct arylation of anilides under external oxidant-free conditions using CO2-Derived Dimethyl Carbonate (DMC) as a 'green' solvent - Sahoo, Manoj K.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Chemistryselect, 2017)
Here, an efficient catalytic protocol for direct C-H bond arylation of anilides under base- and external oxidant-free conditions is reported. This reaction proceeds readily at room temperature using CO2-derived dimethyl carbonate (DMC) as a green solvent under visible-light dual catalysis. Later, application of our strategy for the gram-scale synthesis of Boscalid has been successfully shown. An unprecedented unsymmetrical bis-arylation of anilides is also demonstrated under mild, redox-neutral conditions.

Manganese-catalyzed direct conversion of ester to amide with liberation of H 2 - Mondal, Akash; Subaramanian, Murugan; Avanashiappan, Nandakumar; Balaraman, Kambaram (Organic Letters, 2018)
A simple and efficient Mn-catalyzed acylation of amines is achieved using both acyl and alkoxy functions of unactivated esters with the liberation of molecular hydrogen as a sole byproduct. The present protocol provides an atom-economical and sustainable route for the synthesis of amides from esters by employing an earth-abundant manganese salt and inexpensive phosphine-free tridentate ligand.

Ni-catalyzed dehydrogenative coupling of primary and secondary alcohols with methyl-N-heteroaromatics - Rana, Jagannath; Babu, Reshma; Subaramanian, Murugan; Balaraman, Ekambaram (Organic Chemistry Frontiers, 2018)
Here we report the first base-metal catalyzed dehydrogenative coupling of primary (aromatic, heteroaromatic, and aliphatic) and secondary alcohols with methyl-N-heteroaromatics to form various C(sp(3))-alkylated N-heteroaromatics. The reaction is enabled by Earth abundant, non-precious NiBr2 as a transition metal catalyst and N,N,N,N-tetramethylethylenediamine (TMEDA) as a ligand system. Mechanistic studies reveal that a hydrogen auto-transfer process is involved in the direct C(sp(3))-alkylation and the reaction proceeds through an -olefination process.

Phosphine-free cobalt pincer complex catalyzed Z-selective semi-hydrogenation of unbiased alkynes - Landge, Vinod G.; Pitchaimani, Jayaraman; Midya, Siba P.; Subaramanian, Murugan; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
Herein, we report a novel, molecularly defined NNN-type cobalt pincer complex catalyzed transfer semi-hydrogenation of unbiased alkynes to Z-selective alkenes. This unified process is highly stereo-and chemo-selective and exhibits a broad scope as well as wide functional group tolerance. Ammonia-borane (AB), a bench-stable substrate with high gravimetric hydrogen capacity, was used as a safe and practical transfer hydrogenating source.

Nickel(ii)-catalyzed direct olefination of benzyl alcohols with sulfones with the liberation of H-2 - Landge, Vinod G.; Yadav, Vinita; Subaramanian, Murugan; Dangarh, Pragya; Balaraman, Ekambaram (Chemical Communications, 2019)
A nickel(II)-catalyzed direct olefination of benzyl alcohols with sulfones to access various terminal and internal olefins with the liberation of hydrogen gas is reported.

Reusable cobalt catalyst for reversible acceptorless dehydrogenation and hydrogenation of N-Heterocycles - Jaiswal, Garima; Subaramanian, Murugan; Sahoo, Manoj K.; Balaraman, Ekambaram (ChemCatChem, 2019)
<span style="color: rgb(42, 45, 53); font-family: "Source Sans Pro", Arial, Helvetica, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(248, 248, 248);">The development of robust catalytic systems based on basemetals for reversible acceptorless dehydrogenation (ADH) and hydrogenation of feedstock chemicals is very important in the context of ` hydrogen storage'. Herein, we report a highly efficient reusable cobalt-based heterogeneous catalyst for reversible dehydrogenation and hydrogenation of N-heterocycles. Both the ADH and the hydrogenation processes operate under mild, benign conditions.

Iron-catalyzed direct julia-type olefination of alcohols - Landge, Vinod G.; Babu, Reshma; Yadav, Vinita; Subaramanian, Murugan; Gupta, Virendrakumar; Balaraman, Ekambaram (Journal of Organic Chemistry, 2020)
Herein, we report an iron-catalyzed, convenient, and expedient strategy for the synthesis of styrene and naphthalene derivatives with the liberation of dihydrogen. The use of a catalyst derived from an earth-abundant metal provides a sustainable strategy to olefins. This method exhibits wide substrate scope (primary and secondary alcohols) functional group tolerance amino, nitro, halo, alkoxy, thiomethoxy, and S- and N-heterocyclic compounds) that can be scaled up. The unprecedented synthesis of 1-methyl naphthalenes proceeds via tandem methenylation/double dehydrogenation. Mechanistic study shows that the cleavage of the C-H bond of alcohol is the rate-determining step.

Manganese-catalyzed alpha-olefination of nitriles with secondary alcohols - Yadav, Vinita; Landge, Vinod G.; Subaramanian, Murugan; Balaraman, Ekambaram (ACS Catalysis, 2020)
An expedient catalytic approach for alpha-olefination of nitriles using secondary alcohols with the liberation of molecular hydrogen and water as the only byproducts is reported. This reaction is catalyzed by a molecularly defined manganese(I) pincer complex and operates in the absence of any hydrogen acceptors. A broad range of substrates including cyclic, acyclic, and benzylic alcohols, as well as various nitrile derivatives, such as arylmethyl and heteroarylmethyl nitriles, are employed in the reaction to provide a diverse range of alpha-vinyl nitriles in good to excellent yields. Mechanistic studies showed that the reaction proceeds via dehydrogenative pathway and the activation of alpha(C-H) bond of the alcohol is the rate-determining step.
Keywords: acceptorless dehydrogenation; Alcohol; alpha-olefination; Hydrogen; manganese

Insights into the nature of self-extinguishing external donors for ziegler-natta catalysis: a combined experimental and DFT study - Vipin Raj, K.; Kumawat, Jugal; Dhamaniya, Sunil; Subaramanian, Murugan; Balaraman, Ekambaram; Kumar Gupta, Virendra; Vanka, Kumar; Grubbs, Robert H. (ChemCatChem, 2021)
Developing donors for Ziegler-Natta (ZN) catalysis to control the polymerization reaction and produce polymers with desirable properties has always been challenging due to the multi-component nature of the catalytic systems. Here, we have developed a new synthetic protocol for making two external donors, D-1 (2,2,2-trifluoroethyl myristate) and D-2 (2,2,2-trifluoroethyl palmitate) that show self-extinguishing properties, followed by a systematic DFT study to understand this peculiar property of these donors. D-1 and D-2 can undergo parallel reactions with aluminum and titanium species present in the system to produce ketones and aldehydes, which are poisons for ZN catalytic systems, thus explaining their self-extinguishing nature. The non-covalent interaction between the long alkyl chain of the donors with the surface plays a vital role in determining the donors ` self-extinguishing nature. There is a significant thermodynamic preference for the binding of the donor with the longer alkyl chain at the titanium center. The current work, therefore, provides interesting insights into how self-extinguishing donors function in ZN catalytic systems.
Keywords: DFT; donors; non-covalent interactions; self-extinguishing; Ziegler-Natta catalysis

Tandem acceptorless dehydrogenative coupling-decyanation under nickel catalysis - Midya, Siba P.; Subaramanian, Murugan; Babu, Reshma; Yadav, Vinita; Balaraman, Ekambaram (Journal of Organic Chemistry, 2021)
The development of new catalytic processes based on abundantly available starting materials by cheap metals is always a fascinating task and marks an important transition in the chemical industry. Herein, a nickel-catalyzed acceptorless dehydrogenative coupling of alcohols with nitriles followed by decyanation of nitriles to access diversely substituted olefins is reported. This unprecedented C=C bond-forming methodology takes place in a tandem manner with the formation of formamide as a sole byproduct. The significant advantages of this strategy are the low-cost nickel catalyst, good functional group compatibility (ether, thioether, halo, cyano, ester, amino, N/O/S heterocycles; 43 examples), synthetic convenience, and high reaction selectivity and efficiency.

Dehydrogenative coupling of alcohols with internal alkynes under nickel catalysis: an access to β-deuterated branched ketones - Subaramanian, Murugan; Gouda, Chandrakant; Roy, Triptesh Kumar; Ganesan, Sivakumar; Banerjee, Subhrashis; Vanka, Kumar; Balaraman, Ekambaram (ACS Catalysis, 2024)
In synthetic organic chemistry, unconventional strategies for advanced chemical synthesis pose interesting and challenging problems. Alcohols act as alkylating agents in the C-C and C-N bond-forming reactions via the dehydrogenative borrowing hydrogen strategy in traditional transition metal catalysis; however, as an acylating agent in the C-C bond-forming reactions is challenging and rarely reported. Here, we report the dehydrogenative coupling of benzylic alcohols with internal alkynes under nickel(II) catalysis, wherein alcohol is used as an acylating agent. This reaction system affords a wide range of alpha-branched aryl ketone derivatives with zero waste generation through the umpolung borrowing hydrogen strategy. Moreover, we have demonstrated the chemodivergent applications of the alpha-disubstituted ketones to other valuable building blocks, including large-scale synthesis of beta-deuterated branched ketones. Several spectroscopic studies, intermediate identification, and density functional theory calculations were performed to elucidate the reaction mechanism.
Keywords: Alcohols; alpha-branched aryl ketones; dehydrogenative coupling; internal alkynes; nickel catalysis; pseudoumpolung

Nickel-catalyzed tandem conversion of paraformaldehyde : methanol to hydrogen and formate/chemo- and stereoselective hydrogenation of alkynes under neutral conditions - Subaramanian, Murugan; Padhy, Subarna Sukanya; Gouda, Chandrakanth; Das, Tamal; Vanka, Kumar; Balaraman, Ekambaram (Catalysis Science and Technology, 2024)
The development of new catalytic protocols for clean and COx-free hydrogen generation from fundamental feedstocks is always interesting and challenging. Herein, we disclose nickel-catalyzed dihydrogen generation from a mixture of paraformaldehyde-methanol under base-free and activator-free conditions. The dihydrogen generation from this redox combination under neutral, oxidative coupling conditions has been integrated with the hydrogen transfer reactions such as chemo- and stereoselective hydrogenation of alkynes in a tandem manner. This unprecedented strategy provides diverse highly stereoselective olefins with excellent tolerance of reducible functional groups such as ether, silyl ether, aldehyde, keto, ester, nitrile, halides including bromo and iodo groups, and heteroarenes. Additionally, we demonstrated catalytic stereo-interconversion of alkenes under benign conditions. The affordable gram-scale synthesis of some important pharmaceutical bioactive molecules has further enhanced their synthetic value. A tandem dihydrogen generation from a mixture of paraformaldehyde-methanol under base-free conditions followed by semihydrogenation of alkynes is reported.